A distributed control for accurate active‐power sharing in islanded microgrids subject to clock drifts. Issue 3 (28th January 2021) - Alfaro, Carlos; Castilla, Miguel; Camacho, Antonio; Marti, Pau; Velasco, Manel
Abstract: Inverters‐based islanded microgrids are operated by local digital signal processors, driven by their own local clocks. These local clocks have drifts affecting the clock signals which are used to control the inverters in real time. In this scenario, a steady‐state deviation is observed in active power sharing, degrading the microgrid performance. This paper presents a new control scheme that improves the microgrid performance by cancelling the active power sharing error due to clock drifts. The study includes a theoretical stability analysis and a design procedure of the control parameters based on the dynamic characteristics. Finally, selected experimental results are obtained in a laboratory microgrid with four inverters. In this setup, each inverter was equipped with its digital signal processor with drifting local clock.